Factors Influencing the Large of Income and Remittance of Karangasem Migrant Workers in Denpasar City - Putri Gayatri Wijayanti; Ida Bagus Putu Purbadharmaja (International Journal of Management Research and Economics, 2025)
Denpasar City is one of the main destinations for migrants in Bali Province. This is because the development carried out tends to be centered in Denpasar City, which is reflected in the concentration of various activities that act as the center of government, economy, trade, education activities, health services, and tourism activities. The objectives of this study are to: 1) Analyze the influence of education level, number of family dependents in the area of ​​origin, allocation of working hours, on the amount of income of Karangasem migrant workers in Denpasar City. 2) Analyze the influence of education level, number of family dependents in the area of ​​origin, allocation of working hours, on the amount of remittances of Karangasem migrant workers in Denpasar City. 3) Analyze the indirect influence of education level, number of family dependents in the area of ​​origin, allocation of working hours on remittances through the income of Karangasem migrant workers in Denpasar City. The determination of the sample in this study used the Accidental Sampling technique. The type of data used is quantitative data with primary data sources. Data collection was carried out using observation methods, structured interviews and in-depth interviews. The data used were then analyzed using path analysis techniques. The results of the study found that 1) education level, number of family dependents, and allocation of working hours have a positive and significant effect on the income of Karangasem migrant workers in Denpasar City. 2) education level has a positive and insignificant effect on remittances of Karangasem migrant workers in Denpasar City, the number of family dependents in the area of ​​origin has a positive and significant effect on remittances of Karangasem migrant workers in Denpasar City, and allocation of working hours has a negative and significant effect on remittances of Karangasem migrant workers in Denpasar City. 3) Education level, number of family dependents in the area of ​​origin, allocation of working hours have an indirect and significant effect on remittances through the income of Karangasem migrant workers in Denpasar City.